Extended coupled cluster for Raman and infrared spectra of small molecules - Joshi, Sayali P.; Dutta, Achintya Kumar; Pal, Sourav; Vaval, Nayana (Chemical Physics, 2012)
In this paper we study the harmonic vibrational frequencies, infrared (IR) intensities, Raman intensities and depolarization ratio using extended coupled cluster method. Raman and IR intensities are mixed derivatives of energy with respect to the electric field and geometric perturbation whereas vibrational frequencies are derivatives of energy with respect to geometry. We use semi-numerical approach to obtain these derivatives. We have studied the effect of electron correlation and basis set for the above properties. We compare our results with non-variational coupled cluster and experimental values, wherever available. We have studied HF, BH, CH+, CO and H2CO molecules in different basis sets. For HF molecule, benchmarking is done with full CI values and basis set convergence is studied for this molecule. Effect of triples is studied for all the molecules. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Extended coupled cluster; IR and Raman spectroscopy; Mixed derivatives